2006
DOI: 10.1381/096089206778392194
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Surgery Binge Eating Status: Effect on Eating Behavior and Weight Outcome after Gastric Bypass

Abstract: RYGBP surgery has an equally positive impact on eating behavior and weight loss for both BE and NBE. Within a multidisciplinary clinic, preoperative BE status does not appear to be a negative prognostic indicator for RYGBP surgery in the domains of weight loss and disinhibition. Further replication is needed with longer follow-up times and larger samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
4
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 28 publications
5
41
4
15
Order By: Relevance
“…In agreement with other studies assessing the effects of maladaptive eating behaviours on weight loss outcome, e.g. Bocchieri-Ricciardi et al, 2006;White, et al, 2006;Powers et al,1999), pre and postoperative BE were unable to significantly predict weight loss at three and six months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with other studies assessing the effects of maladaptive eating behaviours on weight loss outcome, e.g. Bocchieri-Ricciardi et al, 2006;White, et al, 2006;Powers et al,1999), pre and postoperative BE were unable to significantly predict weight loss at three and six months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have found that higher preoperative levels of BE predicted poorer weight loss (e.g. Hsu, Sullivan, & Benotti, 1997), whereas others have found no evidence to support this (Bocchieri-Ricciardi et al, 2006;White, Masheb, Rothschild, Burke-Martindale, & Grilo, 2006;Powers, Perez, Boyd, & Rosemurgy, 1999) and some have even found better weight loss outcomes (e.g. Latner & Wilson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A presença de compulsão alimentar antes da intervenção cirúrgica, por exemplo, tem sido vista como fator de pior prognóstico, seja com relação à menor redução de peso [6][7][8] , seja com relação à reaquisição dele após a fase de estabilização, em geral devido ao equivalente "beliscar" compulsivo 3,[9][10][11][12][13] . Por outro lado, alguns estudos não encontraram associação consistente entre transtorno da compulsão alimentar periódica no pré-operatório e redução de peso após a cirurgia [14][15][16][17][18][19] . Tais discrepân-cias, em boa medida, se devem à ausência de conformidade entre os estudos com relação ao emprego de instrumentos de investigação 20 .…”
unclassified
“…condição alimentar. Estudo com pacientes submetidos à cirurgia restritiva acompanhados por 10 anos, encontrando episódios bulímicos em 52% dos casos, transtorno do comer compulsivo em 16% e síndrome do comer noturno em 10% 5 .…”
Section: Abcddv/622unclassified
“…O impacto da compulsão alimentar pré-operatória nos resultados da cirurgia é pouco estudado 5,12 . Pacientes submetidos à cirurgia bariátrica necessitam compreender a dinâmica associada ao comportamento alimentar e desenvolver novos hábitos, para evitar que outros transtornos ocorram em compensação ao distúrbio alimentar.…”
Section: Abcddv/622unclassified